Critical success factors for large scale automation experiences from 10,000 gates - Oakes, Tony, author; Ciavarella, Gino, author; Halm, Remy, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
Canals have been the principal means of distributing irrigation water since the early civilisations. However, the performance of irrigation systems, which use approximately 70% of the available water world-wide, is being called into question. The technology used to control canals and hence their performance changed little until the second half of the nineteenth century when the early work on performance enhancement started with the first generation of activities focused on automatic monitoring and regulation. This paper provides an overview of the experiences gained over the last 20 years in the application of technology to enhance the performance of large scale irrigation systems through improvements to monitoring and control. Improving the productivity of irrigated agriculture is seen as a critical initiative to double world food production by 2050. Improving the performance of irrigation canal systems is seen as a critical requirement to meet the future world food needs.
Meeting irrigation demands in a water-challenged environment
Large scale automation experiences
Presented at Meeting irrigation demands in a water-challenged environment: SCADA and technology: tools to improve production: a USCID water management conference held on September 28 - October 1, 2010 in Fort Collins, Colorado.